In pursuit of evidence: A need to transform Ayurvedic education - Sruthi G; Megha (Journal of Ayurveda and Integrative Medicine)
There is a loud call nationally and internationally to strengthen the evidence base for traditional medicine. Ayurveda, like other traditional systems, is often criticized for its lack of evidence upto the standard expected for modern day healthcare drugs and practices. This gap in evidence has led to Ayurveda being viewed as inferior to biomedicine. Therefore, producing high-quality evidence is essential not only for the credibility of Ayurveda but also to elevate its inclusion in standard of care practices globally. Yet, how can this evidence be generated if Ayurvedic researchers and practitioners are not formally taught about the advantages and means of evidence synthesis? The prevailing research culture in Ayurveda largely emphasizes validating ayurvedic formulations by substituting them into well-established clinical protocols for modern disease descriptors, rather than focusing on hypothesis-driven research using ayurvedic vocabulary. We argue that this arises in part from an outdated curriculum, poorly trained teachers, insufficient investment in research infrastructure at teaching colleges, and a paucity of policies to encourage cross-disciplinary learning. To address these gaps, we propose a comprehensive transformation of Ayurvedic education by including biomedical credit courses into the curriculum, practical internships to provide hands-on-experience, recruitment of teachers with biomedical expertise and funds to upgrade Ayurveda colleges. These ideas will help develop a cohort of Ayurveda graduates who are not only familiar with modern biomedicine, but also have the fundamental knowledge to develop, and test new ideas. India can emerge as a global leader in the area of integrative medicine, with its repository of several indigenous medical systems, and talented human capital in biomedical sciences. It is time we take the plunge.